Image Detalization as an Indicator of Figurative and Plastic Creativity of Preschoolers - E.V. Gorshkova (Moscow State University of Psychology and Education, 2024)
Based on a brief description of creativity and imagination, their indicators and age characteristics, the insufficiency of research on the creativity of preschoolers is shown. A diagnostic study (1993–2000) is described, aimed at identifying the age characteristics of children 3–7 years old in detailing the motor-plastic image. 192 children participated in the diagnosis according to the author's method "Hare and Wolf"; they were asked to embody the plot of the "fairy tale" by means of the movement language. It was revealed: in the younger group, schematic movements predominate, signifying the image; in the middle group, the proportion of "complex" figurative movements is growing; in the senior and preparatory groups, "complexes" (partial and integral) prevail and the number of sequences of figurative movements that convey the phases of the character's actions is growing. Statistical analysis (according to the criteria H Kruskal-Wallis and U Mann-Whitney) revealed significant differences in image detail between different age samples and the absence of such differences between boys and girls (in different years).